Total score of athleticism: Profiling strength and power characteristics in professional soccer players after anterior cruciate ligament reconstruction to assess readiness to return to sport - Maestroni, L.; Turner, A.; Papadopoulos, K.; Sideris, V.; Read, P. (The American Journal of Sports Medicine, 2023)
Background: There is no consensus on the optimal testing procedure to determine return-to-sport (RTS) readiness after anterior cruciate ligament (ACL) reconstruction. Current approaches use limb symmetry across a range of tests, but this does not consider a patient`s level of athleticism or benchmarks relative to his or her noninjured counterparts.